Age‐dependent decrease in TRPM4 channel expression but not trafficking alters urinary bladder smooth muscle contractility. Issue 4 (24th February 2021) - Maxwell, Sarah E.; Leo, M. Dennis; Malysz, John; Petkov, Georgi V.
Abstract: During development, maturation, or aging, the expression and function of urinary bladder smooth muscle (UBSM) ion channels can change, thus affecting micturition. Increasing evidence supports a novel role of transient receptor potential melastatin‐4 (TRPM4) channels in UBSM physiology. However, it remains unknown whether the functional expression of these key regulatory channels fluctuates in UBSM over different life stages. Here, we examined TRPM4 channel protein expression (Western blot) and the effects of TRPM4 channel inhibitors, 9‐phenanthrol and glibenclamide, on phasic contractions of UBSM isolated strips obtained from juvenile (UBSM‐J, 5–9 weeks old) and adult (UBSM‐A, 6–18 months old) male guinea pigs. Compared to UBSM‐J, UBSM‐A displayed a 50–70% reduction in total TRPM4 protein expression, while the surface‐to‐intracellular expression ratio (channel trafficking) remained the same in both age groups. Consistent with the reduced total TRPM4 protein expression in UBSM‐A, 9‐phenanthrol showed lower potencies and/or maximum efficacies in UBSM‐A than UBSM‐J for inhibiting amplitude and muscle force of spontaneous and 20 mM KCl‐induced phasic contractions. Compared to 9‐phenanthrol, glibenclamide also attenuated both spontaneous and KCl‐induced contractions, but with less pronounced differential effects in UBSM‐A and UBSM‐J. In both age groups, regardless of the overall reduced total TRPM4 protein expression in UBSM‐A, cell surface TRPM4 protein expression ( 80%) predominated over its intracellular fraction ( 20%), revealing preserved channel trafficking mechanisms toward the cell membrane. Collectively, this study reports novel findings illuminating a fundamental physiological role for TRPM4 channels in UBSM function that fluctuates with age. Abstract : In this study, based on an experimental animal model, we revealed a novel age‐dependent role of TRPM4 channels in UBSM function. Specifically, there was higher expression of TRPM4 channel protein in UBSM from juvenile guinea pigs associated with increased inhibitory effects of a TRPM4 channel blocker on contractility compared to UBSM from older adult animals. Future comparative studies on human UBSM isolated from patients with or without OAB from various age groups will provide insights as to if TRPM4 channel dysfunction is a contributing factor to OAB that increases with age.